Analysis of Determinant Factors for Hospital Staff Adherence to The Use of PPE The Care of COVID-19 Patients - Indra Gunawan; Djazuly Chalidyanto (Universitas Muhammadiyah Yogyakarta, 2020)
COVID-19 (coronavirus2019) is a viral infection of concern globally. Based on data released by the National Disaster Management Agency in July 2020, there was a twenty-six COVID-19 hospital cluster. This study aimed to analyze determinant factors for hospital staff adherence to the use of personal protective equipment in the care of COVID-19 patients. This Study is observational research with a cross-sectional design. The sample was selected using a simple random sampling technique with a total sample of 53 respondents. Data was collected using a questionnaire and analyzed using linear regression statistical analysis. The result of the study illustrated that only 43.40% of the hospital staff were compliant to use PPE. The respondents have characteristics as follows: good knowledge (52.83%), good risk perception (50.94%), low barriers to implementation (71.70%), good safety climate (90.57%), and good information and training (94.34%). There were correlation between knowledge (p-value = 0.000, β = 0.880), risk perception (p-value = 0.000, β = 0.846), barriers to implementation (p-value = 0.000, β = 0.579), safety climate (p-value = 0.005, β = 0.646), information and training (p-value = 0.034, β = 0.620) with hospital staff using PPE. Knowledge and risk perception has a very strong correlation with hospital staff adherence.